Using a Study Abroad Experience as the Stimulus to Globalize the Secondary Agricultural Education Curriculum - Katrina R Sharp; Grady Roberts (Journal of International Agricultural and Extension Education, 2013)
The purpose of this case study was to document how one preservice agricultural education teacher’s study abroad experience was used as a stimulus to globalize a secondary agricultural education curriculum. The lead author participated in a three-week study abroad trip to Costa Rica focused on sustainable agriculture. Upon returning from that trip the researchers developed a four-lesson curriculum on Costa Rican agriculture with lessons focused on Introduction to Latin America, Sustainability, Agroforestry, and Tropical Crops. This curriculum was delivered to a group of ninth grade students in an introductory agricultural education course. The students were taught one lesson per week over a four-week period. Students completed pre- and post-tests to assess their knowledge and a curriculum evaluation survey. Test scores doubled after the curriculum implementation. Additionally, students had favorable opinions about the curriculum. The activities undertaken in this project demonstrate a possible approach to expanding the educational impacts of a study abroad experience. The authors recommend that similar approaches be implemented in other contexts to see if the results can be replicated. The activities undertaken in this project appear to be an effective approach to expose a previously unreached group of young agriculturists to global aspects of their subject. The long-term impacts on these students are beyond the scope of this study but should be examined
Keywords: Global Education; Study Abroad; Secondary Agricultural Education; Curriculum